2014
DOI: 10.1111/jopr.12143
|View full text |Cite
|
Sign up to set email alerts
|

Contrast Ratio of Six Zirconia‐Based Dental Ceramics

Abstract: The thickness and brands had significant effects on the contrast ratio of six zirconia dental ceramics. The mean contrast ratio values of inCoris TZI, Lava™, and Lava™ Plus High Translucency were significantly lower than those of Cercon® Base, Zeno®, and ZENO® Translucent at all thicknesses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
28
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 16 publications
3
28
0
Order By: Relevance
“…This result suggests that Zr1500 has almost the same level of translucency as commercially available translucent Y-TZP. As the thickness of the specimens increased, CR also increased but TP decreased, resulting in a lower level of translucency; this is the same tendency as has been reported in the past 24,25) . In addition, another report 26) states that TZI was found to have a lower CR value but a higher level of translucency than ZI, corroborating the results of our study.…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…This result suggests that Zr1500 has almost the same level of translucency as commercially available translucent Y-TZP. As the thickness of the specimens increased, CR also increased but TP decreased, resulting in a lower level of translucency; this is the same tendency as has been reported in the past 24,25) . In addition, another report 26) states that TZI was found to have a lower CR value but a higher level of translucency than ZI, corroborating the results of our study.…”
Section: Resultssupporting
confidence: 83%
“…In addition, another report 26) states that TZI was found to have a lower CR value but a higher level of translucency than ZI, corroborating the results of our study. Elsewhere 25) , it was reported that TZI, in the thickness range of 0.6 to 1.5 mm, was found to have lower CR values and higher levels of translucency than other commercial translucent Y-TZP products (ZENO Translucent, LAVA Plus High Translucency).…”
Section: Resultsmentioning
confidence: 99%
“…Where Y b and Y w are the spectral reflectance of light of the specimen over a black and white background, respectively . For a transparent material, the CR is 0.0, while for an entirely opaque material, the CR is 1.0 …”
Section: Methodsmentioning
confidence: 99%
“…[33][34][35][36][37] A very high and statistically significant correlation was found between the spectrophotometer and digital imaging analysis for all CIE L*a*b* color values. 27,38 Translucency is material-and thickness-dependent 9,39,40 and vary according to the measuring techniques. 41 Values of zirconia TP reported with spectrophotometer are highly variable and range from 0.23 to 9.66 at 1.5 mm of thickness 42 and from 15.1 to 5.5 for thicknesses varying between 0.4 and 1 mm.…”
mentioning
confidence: 99%